Prevalencia e intensidad parasitaria en Mugil cephalus (Pisces: Mugilidae),. del Río Colorado, Baja California, México - Valles-Ríos, Martha E (2000)
The parasitic prevalence and mean intensity in the striped mullet, Mugil cephalus, was seas,?nally determined during an annual cycle (February 1994 to February 1995) in the confluence of the Colorado and Hardy rivers, Baja California, México. Two species of parasites were identified, a nematode, Contracaecum multipapillatum (von Drasche, 1882) (Ascaridida: Anisakidae), and a copepod, Ergasilus versicolor Wilson, 1911 (Poecilostomatoida: Ergasilidae). The larvae of C. multipapillatum, which were represented by two size classes (A and B stages), had prevalences of 30% and 14.5%, respectiv